2017
DOI: 10.1016/j.ijscr.2017.06.029
|View full text |Cite
|
Sign up to set email alerts
|

A colovesical fistula with a persistent descending mesocolon due to partial situs inversus: A case report

Abstract: HighlightsColovesical fistula was occered in the extremely rare condition: partial situs inversus with persistent descending mesocolon (PDM).Distinctive features of PDM were shortening adhesions noted at the dorsal aspect of the descending and sigmoid mesocolon without marginal vessel.In this case, these congenital abnormalities might help the suture failure during the operation of sigmoid colectomy.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
7
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(9 citation statements)
references
References 17 publications
(19 reference statements)
2
7
0
Order By: Relevance
“…For example, there was anastomotic leakage after sigmoid colon resection for a colovesical fistula in a patient with PDM due to insufficient blood flow caused by the absence of marginal vessels in a previous case report. 6 Thus, our finding further supports that the LCA should be divided after confirming the feeding vessels to the descending colon.…”
Section: Discussionsupporting
confidence: 80%
See 1 more Smart Citation
“…For example, there was anastomotic leakage after sigmoid colon resection for a colovesical fistula in a patient with PDM due to insufficient blood flow caused by the absence of marginal vessels in a previous case report. 6 Thus, our finding further supports that the LCA should be divided after confirming the feeding vessels to the descending colon.…”
Section: Discussionsupporting
confidence: 80%
“…Indeed, there are several case reports of surgery in patients with PDM, 3-10 some of which described the difficulty in performing surgical procedures and the importance of understanding the anatomical features. [6][7][8]10 In addition, a recent study demonstrated that PDM is associated with the difficulty of laparoscopic resection of the sigmoid colon or rectal cancer based on the surgical time and blood loss. 11 On the other hand, several vascular features in PDM were reported such as radial branching pattern of the IMA, short LCA, and short distances between the IMA and inferior mesenteric vein (IMV) and between the IMV and descending colon.…”
Section: Introductionmentioning
confidence: 99%
“…1,2 Due to the characteristic anatomy of PDM, complications such as intestinal volvulus, intussusception, and colovesical fistula have been reported. [3][4][5] In PDM, several branches of the sigmoid colon artery are in close proximity to the LCA and radiate into the pelvis, and the first branch of the sigmoid colon artery often shares a common trunk with the LCA. Additionally, in PDM the descending colon artery, sigmoid colon artery, and superior rectal artery often branch radially from the inferior mesenteric artery (IMA) and are referred to as the radial pattern IMA.…”
Section: Discussionmentioning
confidence: 99%
“…PDM has been described as a failure of fusion of the descending colon mesentery with the posterior and lateral wall peritoneum during this developmental process 1,2 . Due to the characteristic anatomy of PDM, complications such as intestinal volvulus, intussusception, and colovesical fistula have been reported 3–5 …”
Section: Discussionmentioning
confidence: 99%
“…Situs inversus may due to a possible abnormality in rotation in early embryonic life. [ 6 ] Situs inversus totalis is quite compatible with life while situs inversus incompletus often accompanies with cardiopulmonary anomalies.…”
Section: Discussionmentioning
confidence: 99%